Surface plasmon microscopic sensing with beam profile modulation - Zhang, Bei; Pechprasarn, Suejit; Somekh, Michael G. (Optical Society of America, 2012)
Surface Plasmon microscopy enables measurement of local refractive index on a far finer scale than prism based systems. An interferometric or confocal system gives the so-called V(z) curve when the sample is scanned axially, which gives a measure of the surface plasmon propagation velocity. We show how a phase spatial light modulator (i) performs the necessary pupil function apodization (ii) imposes an angular varying phase shift that effectively changes sample defocus without any mechanical movement and (iii) changes the relative phase of the surface plasmon and reference beam to provide signal enhancement not possible with previous configurations.